math

posted by .

Find the inverse of each of these functions
a)f(x)=x/x+2
b)f(x)=2x/5-x
c)f(x)=3x/2x+1

  • math -

    x =2y/5 -y
    5x = 2y -5y
    5x = -3y
    F(x) = -5x/3

  • correction - math -

    1st one:

    if f(x) = x/(x+2) , then y = x/(x+2)

    step1: interchange the x and y variables to get the inverse as

    x = y/(y+2)

    step 2: solve this new equation for y

    x = y/(y+2)
    xy + 2x = y
    xy - y = -2x
    y(x-1) = -2x
    y = -2x/(x-1) or y = 2x/(1-x)

    f^-1 (x) = 2x/(1-x)

    now do the same for others following these two steps.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. graph!

    how can the graph of f(x)= X^2-4X be used to obtain the graph of y=g(x) ?
  2. Math - Inverse Functions

    Find the inverses of the following functions. y = 3(x - 1)^2, x >= 1 Work: x = 3(y - 1)^2 x = 3(y - 1)(y - 1) x = 3(y^2 - y - y + 1) x = 3y^2 - 6y + 3 And now what do I do!?
  3. Algebra

    How do you find the inverse of functions?
  4. math

    consider the functions f(x)=x^3-2 and g(x)=3 sqrt x+2: a. find f(g(x)) b. find g(f(x)) c. determine whether the functions f and g are inverse of each other. I have no clue where to even begin!
  5. Advanced Algebra

    What is the inverse of each of the functions defined by the following equations, if the inverse exists. If the inverse does not exist for the largest possible domain, limit the domain so that the inverse will exist. In each case, give …
  6. Advanced Functions 12

    A student writes, "The inverse of y = -√(x+2) is y = x^2 - 2." Why is this statement false?
  7. Functions - math

    The function f is such that f(x) = a^2x^2 - ax + 3b for x<=(1/2a), where a and b are constants. 1) For the case where f(-2) = 4a^2 - b +8 and f(-3) = 7a^2 - b + 14, find the possible values of a and b. 2) For the case where a = …
  8. Math

    If the inverses of two functions are both functions, will the inverse of the sum or difference of the original functions also be a function?
  9. Functions - math

    The function f is such that f(x) = 2x + 3 for x ≥ 0. The function g is such that g(x)= ax^2 + b for x ≤ q, where a, b and q are constants. The function fg is such that fg(x)= 6x^2 − 21 for x ≤ q. i)Find the values of a and …
  10. Algebra Help ASAP PLEASE!

    ((I forgot how to do find inverse functions and this is important)) Find the inverse function of g(x) = 2x + 4. A) g^(-1)(x) = 4x + 2 B) g^(-1)(x) = 2x + 1/2 C) g^(-1)(x) = 1/2x - 2 D) g^(-1)(x) = 2x - 4 I *think* it might be C but …

More Similar Questions